Efficacy of pembrolizumab rechallenge for metastatic urothelial carcinoma. Issue 5 (25th May 2022) - Nishimura, Nobutaka; Miyake, Makito; Shimizu, Takuto; Tachibana, Akira; Tanaka, Nobumichi; Fujimoto, Kiyohide
Abstract : Introduction: Before the approval of enfortumab vedotin, no standard treatment was available as the salvage treatment for patients with metastatic urothelial carcinoma who had failed second‐line or later pembrolizumab. Pembrolizumab rechallenge is one of the options for these patients, but there is limited evidence on the effectiveness of pembrolizumab rechallenge. We report three patients with metastatic urothelial carcinoma treated with pembrolizumab rechallenge and discuss rechallenge of immune checkpoint inhibitors in other malignancies. Case presentation: This study included three cases treated with pembrolizumab rechallenge with the age of 54 (Case 1), 78 (Case 2), and 67 (Case 3) years old. A complete response to the prior pembrolizumab was observed only in Case 1. However, no patients responded to the pembrolizumab rechallenge. Conclusion: Pembrolizumab rechallenge is not recommended in the current clinical setting of metastatic urothelial carcinoma, even for patients who showed complete response to the prior pembrolizumab.